Evolution of a population of strategies with memory in the presence of a distinct small group - Bezruk, Yurii; Yanovsky, Volodymyr (Bulletin of V.N. Karazin Kharkiv National University, series «Mathematical modeling. Information technology. Automated control systems», 2023)
Topicality. Today, the human population is constantly growing. The influence of societies and subcultures on each other and on the population as a whole is also increasing. It is necessary to expand knowledge in the field of social behavior to improve the understanding of interaction within the population.Key goals. The purpose of the article is to study the influence of selected distinct groups on the evolution of the population. The nature of changes in evolution is studied in the presence of groups of different complexity and size in the population. This work also aims to establish the most evolutionarily advantageous composition and size of a small group and the stage at which a population will be dominated by such a group, if it is possible.Research methods. The evolution of a population with a full set of behavioral strategies, limited only by memory depth, in the presence of a distinct group is considered. Each strategy carrier interacts with all others, themselves included, according to an iterative model of the prisoner's dilemma. Rewards are determined by payment matrices. Each subsequent generation successively loses the most disadvantageous behavioral strategies of the previous generation. Carriers who are members of a distinct group behave more aggressively towards "strangers" and more cooperative with "their own". Different variants of the initial composition of the group are considered, namely the case when the average complexity of a small group is greater than the average complexity of the population as a whole, less, or comparable to it. Variants with different initial size of the small group have been considered – 5, 10, 15, 20% of the population size.The results. The paper shows how the presence of small groups of different complexity and size affects population dynamics. An increase in the aggressiveness of the population has been revealed if there is a small group of any composition in it. The size and composition of a small group that makes it possible to dominate the society and the stage of evolution when it takes place have been established.Conclusion. Based on the results of the article, the main consequences of the influence of distinct small groups on the evolution of the population have been determined.